Decreased mRNA and Protein Expression of BDNF, NGF, and their Receptors in the Hippocampus from Suicide: An Analysis in Human Postmortem Brain - Ritabrata Banerjee; Anup K. Ghosh; Balaram Ghosh; Somnath Bhattacharyya; Amal C. Mondal (SAGE Publishing, 2013)
Despite the devastating effect of suicide on numerous lives, there is still a lack of knowledge concerning its neurochemical aspects. There is increasing evidence that brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) are involved in the pathophysiology and treatment of depression through binding and activating their cognate receptors TrkB and TrkA respectively. The present study was performed to examine whether the expression profiles of BDNF and/or TrkB as well as NGF and/or TrkA were altered in the hippocampus of postmortem brain of the participants, who had committed suicide and whether these alterations were associated with specific psychopathologic conditions. These studies were performed on the hippocampus of 21 suicide victims and 19 non-psychiatric control individuals. The protein and mRNA levels of BDNF, TrkB, NGF, and TrkA were determined by sandwich enzyme-linked immunosorbent assay, Western blot and reverse transcription-PCR. Given the importance of BDNF and NGF and their cognate receptors in mediating physiological functions, including cell survival and synaptic plasticity, our findings of reduced expression of BDNF, TrkB, NGF, and TrkA on both the protein and mRNA levels of postmortem brains of suicide victims suggest that these molecules may play an important role in the pathophysiological aspects of suicidal behavior.